Effectiveness Of Watery Extract And Ethanolic Extract Of Garlic Bulbs (Allium sativum L.) For Second Degree Burns Healing On Mice (Mus musculus) - Noni Zakiah (Universitas Sebelas Maret, 2017)
Bulbs of garlic has been known to contain a compound that is potentially as alternative medicine for burns. This study aimed to determine the effectiveness of the water extract and ethanolic extract of garlic bulbs on second degree burn healing in mice. The test was conducted on 12 male mices divided using a completely randomized design (CRD) into 4 treatment groups consisting of P-1 without any treatment, P-2 by administering Bioplacenton®, P-3 with ethanolic extract and P-4 with watery extract. Lab studies have shown the average percentages of recovery for 18 days for P-2, P-3 and P-4, were 48%, 60% and 63% respectively. One way ANOVA test results obtained p value = 0.011 (p <0.05), it means there were differences in the healing duration of burns in four treatment groups. LSD test results showed that the group which had significant relationship were P-1 and P-4 wherein the Mean Difference was 0.90000. Thus it can be concluded that the group P-4 which is a water extract group was the most effective for the second degree burns healing.